The tommyknockers - King, Stephen 1947- (Putnam, 1987)
Roberta Anderson, while searching for firewood in the forest, stumbles upon a burried ship and with the help of her onetime lover, Jim Gardener, excavates an artifact that changes the townspeople of Haven.